أثر السياق القرآني في تخصيص عموم القرآن عند المحقق الخليلي آية التحريم في سورة الأنعام أنموذجاً: The impact of the Qur’anic context on the specification of the general Qur’an according to Al-Muhaqqiq Al-Khalili: The Model of the verse of prohibition in Surat Al-An’am - AL Hinai, Badriya Ali Waleed; Elatrash , Radwan Jamal (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
ملخص البحث يعد المحقق سعيد بن خلفان الخليلي من العلماء الذين يقصدهم العامة والخاصة من أهل العلم وطلابه في القرن الثالث عشر الهجري من داخل القطر العماني وخارجه، وذلك لتوضيح ما استشكل عليهم من فهم آيات الكتاب العزيز. ولقد كان في كثير من أجوبته يفسر الآيات مستنداً على السياق القرآني، فالمتأمل يجد كتابه تمهيد قواعد الإيمان قد احتوى على كثير من الآيات التي فسرها ورفع ما اشتبه على الأفهام منها. لكن المشكل في الموضوع أن هذه التفاسير المتناثرة في الكتاب لم تعن بالبحث والتحليل والوقوف على منهج المحقق في تفسيرها وتوضيحها. لذا أتى هذا المقال ليقف على آية من آيات سورة الأنعام وهي آية التحريم انتهج المحقق منهج السياق القرآني في رفع اللبس عنها، وتخصيص العموم فيها، وقد تبنى الباحثان في هذا المقال المنهج الاستقرائي والتحليلي للوصول إلى نتائج مهمةً، منها على سبيل المثال: أن للسياق القرآني بنوعيه الداخلي والخارجي أثراً بارزاً في تخصيص العموم، وبيان المجملات، وترجيح المحتملات، ودفع ما يتوهم أنه تعارض بين الآيات. ABSTRACT In the thirteenth century AH, students inside and outside of Oman sought the advice of Sheik Saeed bin Khalfan Al Khalili to help them understand certain Qur’anic verses that they were having trouble comprehending. In many of his answers, he explained the verses based on the Qur’anic context as shown in his book “Tamhid Qawaeid Elliman” which contains many interpretations on that basis. However, these scattered explanations in the book were not concerned with research, analysis, and reliance on the scholar’s approach in interpreting and clarifying them. Therefore, this article examines Sheik Saeed’s approach in using the Qur’anic context to clarify misunderstandings of the Prohibition Verse in Surah Al-An’am as well as the allocation of the commons. Employing an inductive and analytical approach, researchers achieve several significant conclusions including that both internal and external Qur’anic contexts have an essential role in the allocation of the commons, summary explanation, possibilities outweighing as well as disputing any false motion that verses are in opposition